Applied Structure Equation Model for Policy Suggestions to Develop the Digital Economy in Vietnam - Hien, Lam Thanh; Tam, Phan Thanh (Journal of Applied Data Sciences, 2025)
In the current context, promoting innovation in digital economic growth models associated with economic restructuring is a prerequisite for sustainable development. Therefore, the article aims to explore the critical factors influencing the digital economy and proposes policy recommendations for developing the digital economy. The study applies quantitative research methods mainly through actual data surveying of economic experts to evaluate factors affecting the digital economy based on the structural equation model to measure the digital economy in five big cities of Vietnam, including Hanoi, Hai Phong City, Da Nang City, Ho Chi Minh City, and Can Tho City. The data collection strategy involves direct interviews via a structured questionnaire, with a sample size of 800 economic experts, and analysis using SPSS version 20.0 and Amos software. The study's novelty identifies eight critical factors influencing the digital economy at a significance level of 0.01 and eight accepted hypotheses, including (1) Information technology and digital infrastructure, (2) Digital transformation capacity in businesses, (3) Government policies and laws, (4) Human resources, (5) Digital consumer needs and behavior, (6) E-commerce and financial technology, (7) International economic integration, and (8) Market. The findings highlight the significant influence of information technology and telecommunications infrastructure on Vietnam's digital economy. Finally, the authors proposed policy recommendations to enhance the digital economy; moreover, the digital economy is a way of doing business that relies on digital technology and data as its main inputs, operates mainly in a digital environment, and employs information and communication technologies to boost labor productivity, create new business models, and optimize economic structures. This model can be used by agencies, researchers, experts, and economic managers.